The involvement of early stage breast cancer patients during oncology consultations in Italy: a multi-centred, randomized controlled trial of a question prompt sheet versus question listing. Issue 8 (11th August 2017) - Bottacini, Alessandro; Goss, Claudia; Mazzi, Maria Angela; Ghilardi, Alberto; Buizza, Chiara; Molino, Annamaria; Fiorio, Elena; Nortilli, Rolando; Amoroso, Vito; Vassalli, Lucia; Brown, Richard F
Abstract : Objectives: To investigate, prior to an oncology consultation, the use of a pre-prepared list of evidence based questions, Question Prompt Sheet (QPS), compared with a Question List (QL), a patient self-generated list of questions. Design: Multi-centred, randomised controlled trial. Setting: Secondary-care patients attending three outpatient oncology clinics in Northern Italy. Participants: 308 women completed the study. Inclusion criteria were an age between 18 and 75 years, a recent diagnosis of early stage, non-metastatic breast cancer, adequate Italian language skills, no previous oncology visits and no evidence of cognitive impairment. Intervention: Patients received the QPS or the QL prior to the consultation, completed it without suggestion or coaching session and delivered back before the visit.The consultations were audio-recorded and analysed for the number and content of questions. Multilevel linear models were used to compare the two groups. Outcome measures: The primary outcome was the comparison of questions asked between QPS and QL group. Secondary outcomes included satisfaction about questions asked, satisfaction with decision, and level of anxiety. Results: Patients in the QPS and QL group asked 13 and 16 questions respectively. The difference was not significant (b=1.7, CI –0.3 to 3.6, p=0.10). A mean of 22 questions was selected in the QPS, while a mean of 2 questions was written in the QL. Patients in the QPS group were significantly less satisfied (t=3.60, p<0.01) with questions asked but wanted less additional information (t=2.20, p<0.05). Levels of patient decisional satisfaction were equivalent between groups. Similarly, anxiety levels were equal between groups prior to the consultation and decreased in similar way after the consultation. Conclusions: Both interventions have similar impact on patients' participation in terms of question asking during the consultation. Future research is needed in order to explore which components of the interventions are really useful and efficacious. Trial registration: ClinicalTrials.gov NCT01510964